Source to sink: Evolution of lignin composition in the Madre de Dios River system with connection to the Amazon basin and offshore. Issue 5 (21st May 2016) - Feng, Xiaojuan; Feakins, Sarah J.; Liu, Zongguang; Ponton, Camilo; Wang, Renée Z.; Karkabi, Elias; Galy, Valier; Berelson, William M.; Nottingham, Andrew T.; Meir, Patrick; West, A. Joshua
Abstract: While lignin geochemistry has been extensively investigated in the Amazon River, little is known about lignin distribution and dynamics within deep, stratified river channels or its transformations within soils prior to delivery to rivers. We characterized lignin phenols in soils, river particulate organic matter (POM), and dissolved organic matter (DOM) across a 4 km elevation gradient in the Madre de Dios River system, Peru, as well as in marine sediments to investigate the source‐to‐sink evolution of lignin. In soils, we found more oxidized lignin in organic horizons relative to mineral horizons. The oxidized lignin signature was maintained during transfer into rivers, and lignin was a relatively constant fraction of bulk organic carbon in soils and riverine POM. Lignin in DOM became increasingly oxidized downstream, indicating active transformation of dissolved lignin during transport, especially in the dry season. In contrast, POM accumulated undegraded lignin downstream during the wet season, suggesting that terrestrial input exceeded in‐river degradation. We discovered high concentrations of relatively undegraded lignin in POM at depth in the lower Madre de Dios River in both seasons, revealing a woody undercurrent for its transfer within these deep rivers. Our study of lignin evolution in the soil‐river‐ocean continuum highlights important seasonal and depth variations of river carbon components and their connection to soil carbon pools, providing new insights into fluvial carbon dynamics associated with the transfer of lignin biomarkers from source to sink. Key Points: Lignin phenols were analyzed in soils and rivers from the Andes to the Amazon basin Wet‐season POM and dry‐season DOM had fresher and more oxidized lignin downstream, respectively In stratified, white water rivers, undercurrents may export relatively undegraded lignin